Feed additives in pig starter rations - Jensen, A.H.; Koch, B.A.; Harbers, L.H.; Miller, L.A. (Kansas Agricultural Experiment Station, 2011)
Three experiments were conducted to determine the efficacy of certain feed additives, alone or in various combinations, in improving performance of pigs weaned at 4 weeks of age. In the first two, each treatment group of pigs was confined to a 3 ½ by 8-foot concrete-floored pen in the central farrowing unit. In the third experiment 3-by6-foot pens with either flattened expanded metal or wood slat floors were used. A 25-watt light was suspended above the sleeping area in each pen to provide supplementary heat. Wood shavings were used for bedding in the first two experiments, but no bedding was used in the third experiment.
Keywords: Swine; Feed additives; Gain; Daily feed intake